A Systematic Review of Recommender Systems in Education - Vaidhehi, V; Suchithra, R (International Journal of Engineering and Technology, 2018)
Recommender system (RS)s are widely used in different walks of life. This research work is to explore the usage of RS in the field of education. This review is performed in five dimensions which includes, Purpose of RS in Education, various techniques to build RS, input parameters used in design of RS, type of students involved in design of RS and Modelling strategies for RS to represent the data. The outcome of the research work is to facilitate the efficient design of the recommender system in education which will help the students by generating the appropriate recommendations.
Keywords: Recommender System; Modelling Strategy; Techniques; Input-Parameters